Polycystic Ovarian Syndrome ( PCOS ) and Low Glycemic Diet - An Updated Review of literature (Journal of Food and Dietetics Research, 2023)
One of the most prevalent endocrine disorders, polycystic ovary syndrome (PCOS) is linked to an increased risk of metabolic dysregulation. Women who have PCOS have been found to have a higher incidence of obesity. Since eating disorders, such as binge eating, are frequently linked to obesity. Women with polycystic ovarian syndrome (PCOS) are intrinsically insulin resistant and have a high risk of cardiovascular disease and type 2 diabetes. Weight loss improves risk factors and hence low–glycemic index (low-GI) diets are recommended.  The majority of PCOS women are lean, but they may still have central obesity and metabolic problems. In populations that are insulin-resistant, studies of dietary interventions with a low glycemic index (GI) have shown an increase in insulin sensitivity; However, in PCOS-positive women, there is little evidence of this effect. The objective of this review was to determine whether women with PCOS benefit from an isocaloric, low-GI dietary intervention on insulin sensitivity regardless of weight change. A GI diet may help restore menstrual regularity, reduce inflammatory markers and improve insulin sensitivity in women with PCOS.
Keywords: PCOS; polycystic ovary syndrome; nutrition; low Glycemic Index foods